Impact of the Addition of Baricitinib to Standard of Care Including Tocilizumab and Corticosteroids on Mortality and Safety in Severe COVID-19 - Masiá, Mar; Padilla, Sergio; García, José Alberto; García-Abellán, Javier; Navarro, Andrés; Guillén, Lucía; Telenti, Guillermo; Mascarell, Paula; Botella, Ángela; Gutiérrez, Félix (Frontiers in Medicine, 2021)
Background: Baricitinib is a Janus kinase inhibitor with broader anti-inflammatory activity than tocilizumab and antiviral potential, although no head-to-head trials are available. Benefits of adding baricitinib to COVID-19 patients experiencing clinical progression despite standard of care (SOC) including corticosteroids and tocilizumab are also unknown. Methods: Cohort study including microbiologically-confirmed COVID-19 hospitalizations. Primary outcome was 28-day mortality. Secondary outcomes were 60-day and 90-day mortality, the composite outcome "28-day invasive mechanical ventilation (IMV) or death", and safety of the combination. Propensity score-matching was used to identify the association between baricitinib use and the outcomes of interest. Results: Of 1,709 admissions, 994 patients received corticosteroids and tocilizumab, and 110 of them baricitinib after tocilizumab. Propensity score matched 190 (95:95) patients with baricitinib + SOC vs SOC, of whom 69.5% received remdesivir. No significant effect of baricitinib was observed on 28-day (39 events; adjusted hazard ratio [aHR], 0.76; 95% CI, 0.31-1.86), 60-day (49 events, aHR, 1.17; 95% CI, 0.55-2.52) or 90-day mortality (49 events; aHR, 1.14; 95% CI, 0.53-2.47), or on the composite outcome 28-day IMV/death (aHR, 0.88; 95% CI, 0.45-1.72). Secondary infections during hospitalization were not different between groups (17.9% vs 10.5%, respectively; p=0.212) and thromboembolic events were higher with baricitinib (11.6% vs 3.2%; p=0.048), but differences vanished after adjustment (aHR 1.89 [0.31-11.57], p=0.490). Conclusion: Addition of baricinib did not substantially reduce mortality in hospitalized COVID-19 patients with clinical progression despite therapy with tocilizumab and corticosteroids. Combination of baricitinib and tocilizumab was not associated with increased risk of secondary infections or thromboembolic events.